The Relationship between Depression, Anxiety, and Resilience among Pregnant Women During a Public Health Crisis - Saenthaweesuk, Arissara; Lumpo, Wayuree; Kerdsang, Theerayut (Princess of Naradhiwas University Journal, 2026)
Background and Objectives This descriptive correlational study aimed to investigate the relationship between depression, anxiety, and resilience among pregnant women in public health crisis situations, encompassing various forms of crises such as outbreaks of serious infectious diseases, including COVID-19, influenza, SARS, monkeypox, natural disasters, air pollution, social conflict or war, and economic crises. Methods The sample group consisted of pregnant women aged 20 years and older, selected using convenience sampling. The sample size was 1,293 people, divided into 324 from the South and 323 each from the Central, Northern, and Northeastern regions. The research instruments included 4-part questionnaires: Part 1, Personal Information Record; Part 2, resilience measurement; Part 3, depression measurement; and Part 4, State Anxiety Scale. The reliability coefficients using Cronbach’s alpha were .98, .96, and .91, respectively. General data were analyzed using descriptive statistics, and since the data were normally distributed, the Pearson correlation coefficient was used to find the relationship between depression, anxiety, and resilience among pregnant women. Results Depression was negatively correlated with resilience among pregnant women at a statistically significant low level (r = -.23, p < .001), and anxiety was negatively correlated with resilience among pregnant women at a statistically significant moderate level (r = -.30, p < .001). The research findings indicated that if pregnant women had high resilience, they could reduce the occurrence of depression and anxiety during public health crisis situations. Conclusion and Recommendation The research findings should be used to create guidelines for nurses or develop programs for pregnant women to strengthen their resilience and be prepared to face life’s crises.